CRİSİS MANAGEMENT IN JCI ACCREDİTED HOSPİTALS: AN EXAMPLE OF GREAT KAHRAMANMARAŞ EARTHQUAKE COMMUNİCATİON (Third Sector Social Economic Review, 2023)
There are natural-origin crises that institutions and organizations in the service sector may encounter at any time. The earthquake is one of these natural origin crises and the Great Kahramanmaraş earthquake occurred in Türkiye on 06.02.2023. In this direction, the study aims to examine the crisis perception and communication method of hospital-hospital groups towards health tourists in the 06.02.2023 Kahramanmaraş earthquake. In the study, a qualitative research case study design was adopted and document analysis was used as a data collection technique, and content analysis was preferred as a data analysis technique. The sample group consists of the websites and social media (Facebook, Instagram, Twitter, LinkedIn) shares related to Kahramanmaraş earthquake between 06.02.2023 - 06.03.2023 of 22 hospital and-hospital groups that have the Joint Commission Certificate certificate in Türkiye. As a result of the study, two themes with the content of ""Earthquake Injury and Diseases"" and ""Earthquake Psychology"", and four categories with the content of ""Aid in the Earthquake"", ""Hygiene in the Earthquake"", ""Communication in the Earthquake"" and ""Get well soon and Condolences"" were discovered. No findings could be obtained for health tourists, which is the main purpose of the study. In line with these results, some theoretical and practical implications have been made as a policy tool for hospital-hospital groups.
Keywords: JCI Accreditation; Health Tourist; Earthquake; Crisis Management Communication; Hospital Social Media.